2019
DOI: 10.1038/s41433-019-0630-9
|View full text |Cite
|
Sign up to set email alerts
|

5 year incidence of YAG capsulotomy and PCO after cataract surgery with single-piece monofocal intraocular lenses: a real-world evidence study of 20,763 eyes

Abstract: Objectives To evaluate the 3-and 5-year incidence of posterior capsule opacification (PCO) and neodymium-doped yttrium aluminium garnet (Nd:YAG) capsulotomy in patients following cataract surgery, comparing results for different single-piece acrylic hydrophilic and hydrophobic monofocal intraocular lens (IOL) models and other patient factors. Patients and methods Electronic medical record data collected from seven United Kingdom (UK) National Health Service (NHS) ophthalmology clinics for routine, age-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 25 publications
2
68
0
Order By: Relevance
“…Fibrosis often is the result of an aberrant wound healing response characterized by myofibroblast persistence and the excessive production of extracellular matrix proteins like collagen I leading to the loss of tissue structure and function 66,67 . In the lens, the fibrotic disease PCO is a major complication of cataract surgery and is health burden with no effective treatment strategies 68,69 . Our finding that lens resident immune cells serve as myofibroblast progenitors strongly suggests that these cells are mediators of PCO.…”
Section: Discussionmentioning
confidence: 94%
“…Fibrosis often is the result of an aberrant wound healing response characterized by myofibroblast persistence and the excessive production of extracellular matrix proteins like collagen I leading to the loss of tissue structure and function 66,67 . In the lens, the fibrotic disease PCO is a major complication of cataract surgery and is health burden with no effective treatment strategies 68,69 . Our finding that lens resident immune cells serve as myofibroblast progenitors strongly suggests that these cells are mediators of PCO.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies demonstrated that IOL material and design can have a significant effect on posterior capsule opacification (PCO) and neodymium-doped yttrium aluminum garnet (Nd:YAG) capsulotomy rates. [9][10][11][12] AcrySof IOLs were reported to have lower Nd:YAG capsulotomy rates compared with round-edged silicone IOLs (P=0.001). 9 A meta-analysis of randomized controlled trials reported that PCO rates were significantly lower for hydrophobic acrylic versus hydrophilic acrylic IOLs at 1and 2-year follow-up (P=0.0002 and P<0.00001, respectively).…”
mentioning
confidence: 99%
“…Phacoemulsification cataract removal and intraocular lens insertion is the only therapeutic option to address the visual acuity loss due to cataract. Posterior capsule opacity (PCO) can occur after surgery, which is known as being a multifactorial pathology caused by proliferation of residual lens epithelial cells [8,9]. Although the mechanism is still unclear, it is estimated that PCO can occur in about 10% of cases at 1 year and up to 25% at 5 years after cataract surgery [9].…”
Section: Discussionmentioning
confidence: 99%
“…Posterior capsule opacity (PCO) can occur after surgery, which is known as being a multifactorial pathology caused by proliferation of residual lens epithelial cells [8,9]. Although the mechanism is still unclear, it is estimated that PCO can occur in about 10% of cases at 1 year and up to 25% at 5 years after cataract surgery [9]. Laser capsulotomy is usually preformed in the presence of progressive loss of BCVA.…”
Section: Discussionmentioning
confidence: 99%